IBM Desa Tangguh Bencana Melalui Upaya Peningkatan Derajat Kesehatan Masyarakat Yang Optimal - Ainnur Rahmanti; Margiyati Margiyati; Anisa Mutiara Hanani; Auliya Rahma Putri; Ni Kadek Krisna Dwi Patrisia; Dana Faricha; Mutiara Andryani (Pusat Riset dan Inovasi Nasional, 2022)
Abstract: Improving the ability to deal with volcanic disasters needs to be prepared between socialization to people who live around the foot of Mount Merapi. Evacuation drills, public kitchen preparation, stretcher and tent management, refugee management, and village government coordination are some examples of training for the community as an effort to deal with volcanic eruptions. In the preparedness cycle is a series of actions taken to anticipate disasters through organization and through appropriate and effective steps. Early warning is a series of activities to provide warnings as soon as possible to the public about the possibility of a disaster at a place by an authorized institution. The implementation of disaster management in a situation where there is the potential for a disaster to occur as intended includes: preparedness, early warning, preparedness, preparation and testing of disaster emergency management plans, organizing, installing and testing early warning systems, providing and preparing supplies to meet basic needs, organizing, training, and rehearsals on emergency response mechanisms, preparing evacuation locations, compiling accurate data, information, updating fixed procedures for disaster emergency response, and equipment to fulfill the restoration of infrastructure and facilities. Public health in the face of disaster situations also needs to be improved in order to create a disaster-ready, benari and resilient community.